Evaluating Learning Outcomes and Intrinsic Motivation: A Case Study of DS-Hacker 3D - Haahr, Mads (Springer Verlag, 2023)
This paper presents a comprehensive evaluation of an educational video game, DS-Hacker 3D, that incorporates analogies to enhance the learning of conceptual knowledge in computer science, specifically Binary Search Tree (BST) concepts. The study addresses the challenges students face in understanding complex computer science topics and the limited availability of well-evaluated educational video games in the field. DS-Hacker 3D targets undergraduate students and follows a constructivist learning approach, establishing connections between new information and familiar knowledge through analogies. The evaluation includes validated assessment tools to measure learning outcomes and intrinsic motivation. The results demonstrate the effectiveness of the educational video game in facilitating the acquisition of BST conceptual knowledge and promoting intrinsic motivation. The study contributes to the development of educational video games for teaching computer science concepts.
Lecture Notes in Computer Science (LNCS)
Joint Conference on Serious Games (JCSG)
Keywords: Analogies; Binary Search Tree; Digital Game-Based Learning; Educational Video Games